汉字与印尼语书写系统比较 - Karina Fefi Laksana Sakti (Journal of Chinese Language and Culture Studies, 2022)
汉字不仅是汉语书写的基本单位，也是承载文化的重要工具。汉字的数量很多，历史悠久，约有六千多年的历史。汉字和印尼语书写系统具有很大的差异，而汉字的学习对外国学生而言具有一定难度，这也是学习汉语的难点之一。本文使用的研究方法主要是对比分析法。首先梳理汉字的特点和印尼语书写系统的特点，在此基础上，通过对比汉字和印尼语书写系统的特点分析两者之间的差异。本研究发现：汉字与印尼语书写系统的差异主要表现在文字性质、文字形状、 文字或语言的音节、 书写语言时空格的使用以及及文字与方言的关系。 Chinese characters are not only the basic unit of Chinese writing but also an important tool for carrying culture. There are a lot of Chinese characters with a long history, about six thousand years of history. Chinese characters are very difficult for foreign students, including Indonesian students, and it is also one of the difficulties in learning Chinese. Chinese characters and Indonesian writing systems are quite different. The research methods used in this article are descriptive and comparative analysis. First, describe the characteristics of Chinese characters and the characteristics of the Indonesian writing system. After comparing the characteristics of Chinese characters and the Indonesian number writing system, the differences between Chinese characters and the Indonesian writing system are found. This study found that the differences between Chinese and Indonesian writing systems are mainly manifested in the nature of the characters, the shape of the characters, the syllables, spaces needed when writing, and the relationship between the text and the dialect.